PENGARUH ENTREPRENEURIAL EDUCATION, RISK TOLERANCE DAN SELF EFFICACY TERHADAP ENTREPRENEURIAL INTENTION PADA MAHASISWA - Noormalita Primandaru (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
ABSTRACT The role of entrepreneurs in advancing the Indonesian economy is an important thing that cannot be denied. Various programs to raise the spirit of entrepreneurship have been carried out. It is hoped that students as young people will be able to print jobs and no longer be oriented as job seekers. The settings used are natural settings which are also called field research. In terms of time dimensions, this study belongs to the cross-sectional research category. The sampling technique uses a non probability sampling type of purposive sampling. The sample in this study was an economic high school student in Yogyakarta. The analytical model used is the Partial Least Square (PLS) analysis model following a variant-based structural equation (SEM) model which can simultaneously test the measurement model while testing structural models. The results of this study indicate that entrepreneurial education variables have no effect on student entrepreneurial intention, entrepreneurial education variables affect student self-efficacy, risk tolerance variables affect student entrepreneurial intention, and risk tolerance variables affect student self-efficacy.